Nitric oxide debilitates the neuropathogenic schistosome Trichobilharzia regenti in mice, partly by inhibiting its vital peptidases - Macháček, Tomáš; Šmídová, Barbora; Pankrác, Jan; Majer, Martin; Bulantová, Jana; Horák, Petr (Parasites & vectors, 2020)
BACKGROUND: Avian schistosomes, the causative agents of human cercarial dermatitis (or swimmer's itch), die in mammals but the mechanisms responsible for parasite elimination are unknown. Here we examined the role of reactive nitrogen species, nitric oxide (NO) and peroxynitrite, in the immune response of mice experimentally infected with Trichobilharzia regenti, a model species of avian schistosomes remarkable for its neuropathogenicity. METHODS: Inducible NO synthase (iNOS) was localized by immunohistochemistry in the skin and the spinal cord of mice infected by T. regenti. The impact of iNOS inhibition by aminoguanidine on parasite burden and growth was then evaluated in vivo. The vulnerability of T. regenti schistosomula to NO and peroxynitrite was assessed in vitro by viability assays and electron microscopy. Additionally, the effect of NO on the activity of T. regenti peptidases was tested using a fluorogenic substrate. RESULTS: iNOS was detected around the parasites in the epidermis 8 h post-infection and also in the spinal cord 3 days post-infection (dpi). Inhibition of iNOS resulted in slower parasite growth 3 dpi, but the opposite effect was observed 7 dpi. At the latter time point, moderately increased parasite burden was also noticed in the spinal cord. In vitro, NO did not impair the parasites, but inhibited the activity of T. regenti cathepsins B1.1 and B2, the peptidases essential for parasite migration and digestion. Peroxynitrite severely damaged the surface tegument of the parasites and decreased their viability in vitro, but rather did not participate in parasite clearance in vivo. CONCLUSIONS: Reactive nitrogen species, specifically NO, do not directly kill T. regenti in mice. NO promotes the parasite growth soon after penetration (3 dpi), but prevents it later (7 dpi) when also suspends the parasite migration in the CNS. NO-related disruption of the parasite proteolytic machinery is partly responsible for this effect.
Keywords: centrální nervový systém; kyselina peroxydusitá; proteasy; mícha; Schistosoma; Birds; proteiny červů; Humans; synthasa oxidu dusnatého; kůže; Nitric oxide synthase; Mice; zvířata; oxid dusnatý; Nitric Oxide; Guanidines; Trematode Infections; ptáci; infekce červy třídy Trematoda; Central Nervous System; 3-Nitrotyrosine; Nitric Oxide Synthase; Skin; Schistosomiasis; Cathepsin B; Peptide Hydrolases; myši; Schistosomatidae; Trichobilharzia; guanidiny; Animals; Peroxynitrous Acid; lidé; Nitric oxide; schistosomóza; Peroxynitrite; Spinal Cord; Helminth Proteins